Motivational factors for blood donation in first‐time donors and repeat donors: a cross‐sectional study in West Pomerania. Issue 6 (7th August 2017) - Suemnig, A.; Konerding, U.; Hron, G.; Lubenow, N.; Alpen, U.; Hoffmann, W.; Kohlmann, T.; Greinacher, A.
Summary: Objectives: This study aimed to analyse motivational factors for blood donation in different donor groups. Background: As the demographic change will result in a decrease of the population in age groups of blood donors, the risk of blood product shortage increases. Methods: During a 12‐month period, every sixth blood donor presenting at the blood donation centre of the University Hospital was asked to complete a self‐administered questionnaire assessing motivational factors for blood donation. Despite the formalised enrolment protocol, frequent donors were over‐represented in the study cohort, which was adjusted by weighting donors with different numbers of donations per year in such a way that the distribution of numbers of donations per year was the same in the sample as in the donor population. Results: Of 2443 participants, 14·3% were first‐time and 85·3% repeat donors. To "help other people" (>90%) and receiving "medical assessment of my blood values" (63–69%) were the strongest motivational factors in all donor groups. Receiving remuneration (49·2% vs 38·1%) was more important for repeat donors than for first‐time donors, whereas it was the opposite for "being taken by a friend to the donor clinic" (47·0% vs 15·5%). A potentially important observation is that 33·9% of frequent donors reported feeling physically better after blood donation compared to infrequent donors (29·5%). Conclusion: Identification of motivational factors can lead to the design of targeted motivation campaigns for blood donation. The underlying cause of the perceived well‐being after blood donation requires further studies.